Network Markets and Consumer Coordination - Attila Ambrus; Rossella Argenziano (Hungarian Academy of Sciences, Institute of Economics, 2004)
This paper analyzes pricing decisions and competition in network markets, assuming that groups of consumers can coordinate their choices when it is in their interest, if coordination does not require communication. It is shown that multiple asymmetric networks can coexist in equilibrium. A monopolist might operate multiple ex ante identical networks to price differentiate. In Bertrand competition different firms might target high reservation value consumers on different sides of the market. Firms can obtain positive profits in price competition. Product differentiation in equilibrium is endogenized by consumers' network choices. Enough heterogeneity in reservation values is necessary for existence of these asymmetric equilibria.
Keywords: D43; D62; L11; L14; 330; two-sided markets; network externalities; platform competition; coordination; Netzwerkökonomik; Verbraucher; Koordination; Monopol; Duopol; Theorie